탄소 저감형 재료를 활용한 콘크리트의 현장 적용성에 관한 실험적 연구 - 전중규(코오롱건설; 전찬기 (한국재난정보학회 논문집, 9(2), 2013)
최근 건설공사에서의 산업부산물의 활용 실적은 그 동안 연구 성과에 비해 상당히 미비한 실정이다. 한편, 각종 건설현장에서는 탄소 저감형 건설재료 활용 및 적용 효과에 대하여 다양한 방안을 제시하고 있으며 이에 대한 적용 확대 연구도 활발히 진행되고 있다. 본 연구에서는 기존 연구 결과를 바탕으로 산업부산물인 플라이애쉬 및 고로슬래그 미분말이 혼입된 2성분계 및 3성분계 콘크리트에 대하여 역학적 특성, 탄산화 및 염화물 침투 저항성을 통하여 콘크리트 구조물에의 적용성을 평가하였다. 또한 수재슬래그 콘크리트의 현장 적용을 통하여 그 타당성을 검증하였다. The current contractor for use in performance compared to the performance study of industrial byproducts. Due to the stagnation of the construction business and the rise of raw materials, the contractor of the cost savings and environmental issues, and present a variety of ways for research actively being. Through special about the compressive strength characteristics of the mixed concrete, carbonation resistance and chloride penetration resistance of this study, previous studies have been a lot of progress, industrial byproducts, fly ash and blast furnace slag concrete structures were applied to evaluate. KCI Citation Count: 1